2011
DOI: 10.1111/j.1365-2869.2011.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute sleep restriction effects on emotion responses in 30‐ to 36‐month‐old children

Abstract: SUMMARY Early childhood is a period of dramatic change in sleep and emotion processing, as well as a time when disturbance in both domains are first detected. Although sleep is recognized as central in emotion processing and psychopathology, the great majority of experimental data have been collected in adults. We examined the effects of acute sleep restriction (nap deprivation) on toddlers’ emotion expression. Ten healthy children (7 females; 30–36 months) followed a strict sleep schedule (≥12.5 hrs time in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 31 publications
7
151
2
Order By: Relevance
“…Furthermore, it is noteworthy that active (or REM) sleep occupies the biggest portion of a child's sleep and occurs much earlier in human development than proper dreaming (Foulkes 1993). Altogether, these data suggest that REM sleep of infants is likely to subserve crucial emotional (Berger et al 2012;Perogamvros 2012) and learning functions (Fifer et al 2010), much like what is found in adults (Sterpenich et al 2009;Wagner et al 2001) (see Sect. 3.5).…”
Section: Emotional Maturationmentioning
confidence: 86%
“…Furthermore, it is noteworthy that active (or REM) sleep occupies the biggest portion of a child's sleep and occurs much earlier in human development than proper dreaming (Foulkes 1993). Altogether, these data suggest that REM sleep of infants is likely to subserve crucial emotional (Berger et al 2012;Perogamvros 2012) and learning functions (Fifer et al 2010), much like what is found in adults (Sterpenich et al 2009;Wagner et al 2001) (see Sect. 3.5).…”
Section: Emotional Maturationmentioning
confidence: 86%
“…[5][6][7] Nap deprivation in 36-month-old children results in increased expressed negativity to the presentation of neutral and negative pictures and decreased expressed positivity to positive pictures. 8 Furthermore, when facing an emotional challenge (solvable and unsolvable puzzles), nap-deprived children displayed dampened positive emotions to solvable puzzles as well as increased negative emotions to unsolvable puzzles. Vriend and colleagues 9 reported that 1 hour of sleep restriction for 4 consecutive nights resulted in increased sleepiness, less positive affective response to stimuli, and increased difficulty in emotion regulation, in children aged 8 to 12 years.…”
Section: Sleep Disturbances In Infants Arementioning
confidence: 99%
“…The largest challenge is the absence of specific data surrounding adoption, such as birth parent history, pregnancy history, age of adoption, or history of institutionalization, any of which could be expected to affect neurodevelopmental outcomes. 1,[3][4][5] Another limitation is that the ATN data analyzed here were collected at baseline visits, preventing longitudinal analysis of individual participants, which could clarify whether ASD and co-occurring symptoms evolve over time in this population. Furthermore, we lacked a control group of adopted children without ASD, the majority of whom we would expect to develop typically.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of risk factors are more likely to have been experienced by adopted children, such as prenatal drug exposure, early abuse or neglect, and institutional care. [1][2][3][4][5] The risks associated with adoption range from early developmental issues, such as failure to thrive or general developmental delay, to symptoms emerging later in childhood or adolescence, including affective or attachment problems. These risks and outcomes of adoption overlap with characteristics of ASD; however, very little research has evaluated the relationship between the 2 populations.…”
mentioning
confidence: 99%